Civil-military relations in Indonesia: promoting a professional military character from the new order era to the reform era - Yusa Djuyandi; Shanty Kartika Dewi; Luis Fiska Rahayu; Mohd Sufiean Hassan (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
Civil-military relations in Indonesia have experienced ups and downs during several periods of government, namely since the old order, new order, and reform order eras. Military involvement in the political sphere during the new order government has sparked criticism of the professionalism of the Indonesian National Army, as it is considered to have been used as a tool to maintain power through repressive actions. This study uses qualitative methods with literature review techniques to analyze the state of civil-military relations in Indonesia from the new order era to the reform era in an effort to shape a reformist military character. Military control over civilians during the new order era was driven by the need to create political stability and security for the sake of development. However, after the new order era, Indonesia continued to make major changes in realizing a professional national army. In the reform era, the military was under civilian control, which did not allow active military personnel to enter the political and public bureaucratic areas.